AB0975 INITIAL BIOLOGICAL THERAPY RESPONSE IN PATIENTS WITH SUSPECTED AUTOINFLAMAMTORY DISEASE. (June 2019) - Silveira, Laura Fernández; García Ruiz-Santa Quiteria, Maria Isabel; Lovillo, Marisol Camacho; Moreno, Paula Sánchez; Montes Cano, Marco Antonio; Lucena Soto, Jose Manuel; Wittel, Jose Bernabeu; Cabello, Beatriz Muñoz; López-Viota, Julia Fijo; Neth, Olaf
Abstract : Background: The choice of the initial biological therapy for patients with suspected autoinflammatory diseases and not conclusive genetic test remains challenging. Objectives: To assess the clinical response to the initial biological therapy in pediatric patients with suspected autoinflammatory disease with no genetic diagnosis. Methods: We retrospectively reviewed the clinical charts of patients followed in our clinic who started empirical biological therapy after being diagnosed with suspected autoinflammatory disease(sAID) due to the intensity of their symptoms and no response to colchicin or FAMEs. Next generation sequencing using an immune deficiency/dysregulation(115 genes) and autoinflammatory panel(12 genes) was negative/inconclusive in all patients. Results: We identified 9 patients:6/9 were male, median age at fever onset 1.33 years old IQR(0.46-4), age at diagnosis of sAID 3.8 years old IQR(1.75-7). Clinical presentation included fever(9/9), abdominal pain and arthromyalgia(7/9), aphthous(6/9), headache, rash and adenopathy(5/9), delayed growth(4/9), tonsillitis and pericarditis(3/9) as well as diarrhea and pleuritis(2/9). One patient presented with stroke, cutaneous lesions, vasculopathy and haemolytic uraemic syndrome and 1 patient with amyloidosis and secondary hepatosplenomegaly. None of the children suffered from uveitis or meningitis. The flares lasted a median of 14 days(IQR 8-20). Two patients had persistent symptoms. Their mean/median lab values are shown at table. 4/9 patients had homozygous mutations with uncertain significance, heterozygous mutations or polymorphism but their symptoms or familiar study was not suggestive of the corresponding AID. One patient had an heterozygous mutation in MEFv (p.P3696, p.R408q) and also a CECR1 heterozygous mutation with uncertain significance, one patient had pR92Q heterozygous mutation in TNFRSF1A, one patient had MEFv pR202Q homozygous mutation, other patient had a NOD-2 heterozygous mutation and the patient with amyloidosis had INO80 deficiency and a NOD2 mutation (p.A918D). All patients responded to steroid therapy; subsequently 8/9 received anti IL-1Receptor kineret as first biological therapy and 1/9 with suspected vasculopathy received anti-TNF. Response to IL-1R antagonist was complete in 3/8 and partial in 4/8 children;1/8 showed no response. 2/8 patients were switched to anti-TNF: One each to etanercept and Infliximab with good response. The patient with amyloidosis was changed to anti IL-6R with incomplete response but clear improvement compared to anti Il-1R response. The patient with suspected vasculopathy and initial anti-TNF treatment had partial response with no recurrent stroke but persistent skin lesions. Conclusion: An important group of patients with sAID lack genetic confirmation. Empirical use of IL-1R antagonist is promising but not effective in all patients as it was observed in our case series, where 5/8 children showed partial or no response, 3/5 needing a second biologic treatment in form of anti-TNF due to persistent moderate-severe symptoms. A model to predict the response to different therapeutic strategies, based on clinical features and immunological profile (including inflammatory cytokines) might help to choose the most appropriate immunomodulatory treatment. Disclosure of Interests: None declared